Analyze the Relationship Between Exchange Rate and Interest Rate with the Economic Growth of Lao PDR - Sirivongsa, Douangkham; CHANTHAVONE , Thongphanh; XIONGTOUA, Tongvang; HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
In this study aims to study changes in exchange and interest rates with the economic growth of Lao People's Democratic Republic (Lao PDR) and analyze the relationship between exchange rate, interest rate​ with the economic expansion of Lao PDR. The data used in the study are time series data from 1997 to 2023, by using descriptive statistics to analyze changes and quantitative analyze is used on multiple regression equations on a Vector Autoregressive Model (VAR). The study found that: Exchange rate of Lao PDR trend be a higher average change which causes the kip to weaken continuously while interest rate especially loans interest rate will be a change in the upward direction in the early stages and has been a downward change in the recent trend; Lao PDR economic growth, there is continuous growth excepted during when there is no economic crisis or financial crisis including the outbreak of a pandemic and natural disasters. Estimated results in the relationship model of economic growth can be seen that the exchange rate is a relationship with economic growth with a statistical significance level of 0.1. If the exchange rate increases or decrease by 1%, holding other factors constant will affect in increased economic growth in the current year or decrease 0.1640 %; Interest rate is a correlation with economic growth in the current year and according to the given assumptions; it means: If the interest rate in the previous year increased or decrease by 1%, holding other factors constant will affect in economic growth in the current year increase or decrease 0. 4189 % And there is a relationship in the same direction that is according to the given assumptions.